The Routledge handbook of Hellenistic philosophy - Arenson, Kelly E. (Routledge, 2020)
Hellenistic philosophy concerns the thought of the Epicureans, Stoics, and Skeptics, the most influential philosophical groups in the era between the death of Alexander the Great (323 BCE) and the defeat of the last Greek stronghold in the ancient world (31 BCE). The Routledge Handbook of Hellenistic Philosophy provides accessible yet rigorous introductions to the theories of knowledge, ethics, and physics belonging to each of the three schools, explores the fascinating ways in which interschool rivalries shaped the philosophies of the era, and offers unique insight into the relevance of Hellenistic views to issues today, such as environmental ethics, consumerism, and bioethics. Eleven countries are represented among the Handbook's35 authors, whose chapters were written specifically for this volume and are organized thematically into six sections: The people, history, and methods of Epicureanism, Stoicism, and Skepticism. Earlier philosophical influences on Hellenistic thought, such as Aristotle, Socrates, and Presocratics. The soul, perception, and knowledge. God, fate, and the primary principles of nature and the universe. Ethics, political theory, society, and community. Hellenistic philosophy's relevance to contemporary life. Spanning from the ancient past to the present, this Handbook aims to show that Hellenistic philosophy has much to offer all thinking people of the twenty-first century.